The Bias in Composite Performance Measures - Klemkosky, Robert C. (Journal of Financial and Quantitative Analysis, 1973)
Within the past decade, considerable progress has been made in measuring ex post portfolio performance. The two parameter risk-return dimension of investment performance as pioneered by Markowitz has been reduced to a single parameter which incorporates measures of both risk and return. Several different but related one-parameter measures of performance have been developed, notably by Sharpe [8], Treynor [11], and Jensen [3], and are commonly referred to as composite performance measures. Theoretically, the composite measures allow portfolios with different risks and returns to be compared directly.